The Evolution of Advertising Language in the Age of Generative AI: A Sociolinguistic Approach - Koswara, Asep (Jurnal Silatene Sosial Humaniora, 2025)
The rapid advancement of generative AI has significantly transformed advertising language, reshaping communication strategies and consumer engagement. This study examines the linguistic shifts introduced by AI-generated advertisements through a sociolinguistic perspective. The research highlights how AI-driven advertising optimizes personalization and efficiency while often lacking the emotional depth and rhetorical nuance of human-crafted content. By comparing traditional and AI-generated advertising discourse, this study identifies emerging linguistic trends and their implications for audience reception and brand authenticity. Additionally, ethical concerns surrounding privacy and manipulation in AI-generated content are explored. The findings suggest that while AI enhances advertising scalability, balancing automation with human creativity remains crucial for maintaining consumer trust and engagement. This research contributes to the broader discourse on digital communication, providing insights into the evolving role of AI in shaping persuasive language.